City and Art : Istanbul, Mersin, Malmö, London, Vienna workshops. - Zeytinoglu, Emre; Fidan, Mürteza; Mimar Sinan Fine Arts University, Istanbul (Istanbul : Mimar Sinan Fine Arts University, 2009)
Tuna, Ferah ; Koç, Derya ; Aygenli, Serap ; Laberg, Aste ; Fourie, Jeanne ; Götze, Maxie ; Mullane, Aaron ; Gunes, Viktoria ; Endes, Yesim ; Drinkrow, Jeuné ; et al.
I.h.k.v. het City and Art project in Istanbul, 2009
kunstcatalogus